A case of functional neck extension myoclonus with clear effect of distraction. Issue 3 (31st January 2019) - Inoue, Manabu; Morihata, Hirokazu; Matoba, Shun; Shibasaki, Hiroshi
Abstract: We report a 46‐year‐old man who presented repetitive jerky extension movements of the neck in lying position over a period of 10 years. His coexisting diseases included alcoholism and depression. Neurologically, there were repetitive, shock‐like, neck extension movements in the supine or recumbent position, which disappeared in the prone or sitting position. The jerks were not seen during sleep. There was a clear effect of distraction on the jerks, suggesting a psychogenic disorder.